PERUBAHAN GAYA HIDUP MAHASISWA JURUSAN SOSIOLOGI UNIVERSITAS NEGERI MALANG DENGAN HADIRNYA BUDAYA POPULER JEPANG - Muhammad Rizal Hifandi Jusuf; Devina Agustya Ulin Nikma; Imarotul Mahbubah; Nurlita Eka Paluvy; Salsabilla Hana Surya (Jurnal Sosialisasi: Jurnal Hasil Pemikiran, Penelitian dan Pengembangan Keilmuan Sosiologi Pendidikan, 2022)
This article was created with the aim of analyzing the students of the Department of Sociology Education, State University of Malang who are fond of Japanese popular culture, namely watching anime. This Japanese popular culture is indeed very popular among teenagers. The process of entry is so fast among the younger generation, making this trend very popular. Not only in Indonesia, this anime is popular, but in various parts of the world you may be familiar with the term "anime", even not only among children who like this anime, but teenagers and adults also love anime. this. Anime has brought many changes in student lifestyle, including changes in clothing, haircuts and even hair color, as well as the way of language. In addition to these three things, the frequency of a student watching anime with violent elements can trigger students to do things like what they have witnessed. In this study, researchers used a qualitative research method by conducting in-depth observations and interviews with several students majoring in Sociology from the State University of Malang in order to obtain relevant data. Based on the research we have done, the inclusion of anime among students of the Department of Sociology Education, State University of Malang can have positive and negative impacts depending on each individual.